Development of a Pencak Silat catching technique model based on the 2022 match rules as a learning media - Yuni Utari; Nurul Ihsan; Muhamad Sazeli Rifki; Aldo Naza Putra; Suwirman Suwirman; Wenny Sasmitha (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop a Pencak Silat catching technique model based on the 2022 competition rules. The research used a Research and Development (R&D) approach with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The study was conducted at UPTD KBOR Dispora Sumatera Barat, involving seven expert validators and fifteen athletes as respondents. Data were collected using validation sheets and response questionnaires, then analyzed using descriptive quantitative and qualitative methods. The results showed that the developed model achieved a validation score of 95.57%, categorized as very feasible. Athlete responses also indicated a very high level of acceptance, with an average score of 97.78%. These findings demonstrate that the model is valid and practical as a learning medium to support athletes in understanding and applying catching techniques based on updated competition rules. Therefore, the developed model can be effectively used in Pencak Silat training.